2021
DOI: 10.18502/ijph.v50i5.6121
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Combination of Cisplatin and Piperine Induces Apoptosis in MCF-7 Cell Line

Abstract: Background: Piperine is a natural compound obtained from the Piper nigrum that exhibits anti-proliferative and anti-cancer activity in cancer cell lines. We analyzed the cytotoxic effect of piperine combined with cisplatin compound in the human MCF-7 breast cancer cell line and the underlying mechanism. Methods: The present in vitro study was performed on MCF-7 cell line in Jahrom University of Medical Sciences between, Jahrom, Iran from 2016 to 2017. Cultured MCF-7 cells were seeded into four groups: a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…Moreover, TQ synergistically improved the anticancer activity of doxorubicin and cisplatin in hepatocellular carcinoma HepG2 cells [ 45 ]. Similarly, PIP was also reported to exert chemo-modulatory effects on chemotherapeutic drugs in different cancers [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, TQ synergistically improved the anticancer activity of doxorubicin and cisplatin in hepatocellular carcinoma HepG2 cells [ 45 ]. Similarly, PIP was also reported to exert chemo-modulatory effects on chemotherapeutic drugs in different cancers [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired apoptosis is reported as one of the mechanisms leading to SOR resistance in cancer cells and the antiapoptotic protein, B-cell lymphoma 2, is suggested to modulate this phenomenon [ 50 ]. Many reports have attributed the anticancer effects of TQ and PIP to its selective proapoptotic actions through the regulation of p53, Bcl-2-associated X protein, and B-cell lymphoma 2 equilibrium and activation of the caspase enzymes [ 46 , 56 ]. We have examined the apoptotic and necrotic cell death after individual and combined TQ, PIP, and SOR treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the end, 5 μl of Annexin V‐fluorescein isothiocyanate (FITC) and 5 μl of Propidium Iodide were added to the cell suspension. After the mixture was left to sit in the dark for 15 min, the findings were evaluated using a flow cytometer (BD Biosciences, USA) [64] …”
Section: Methodsmentioning
confidence: 99%
“…After the mixture was left to sit in the dark for 15 min, the findings were evaluated using a flow cytometer (BD Biosciences, USA). [64]…”
Section: Cell Apoptosis Assaymentioning
confidence: 99%
“…These compounds often induce apoptosis and suppress metastasis, inhibiting cancer growth and development (9,10). Many studies have suggested that chemotherapeutic drugs-caused cell death may involve mitochondrial pathway-derived apoptosis (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%